Zen and the art of motorcycle maintenance - Pirsig, Robert M. (Bantam Books, 1984)
One of the most important and influential books written in the past half-century, Robert M. Pirsig's Zen and the Art of Motorcycle Maintenance is a powerful, moving, and penetrating examination of how we live . . . and a breathtaking meditation on how to live better. Here is the book that transformed a generation: an unforgettable narration of a summer motorcycle trip across America's Northwest, undertaken by a father and his young son. A story of love and fear -- of growth, discovery, and acceptance -- that becomes a profound personal and philosophical odyssey into life's fundamental questions, this uniquely exhilarating modern classic is both touching and transcendent, resonant with the myriad confusions of existence . . . and the small, essential triumphs that propel us forward.